Hubungan Dukungan Keluarga Dengan Kecemasan Kehamilan Trimester III Di Puskesmas Mulyorejo, Surabaya - Dewi, Pramesti Apsara; Karimah, Azimatul; Ferdinandus, Euvanggelia Dwilda; Sulistiawati, Sulistiawati (Yayasan Jompa Research and Development, 2025)
Pregnancy in the third trimester has the potential to cause physical and psychological changes that cause anxiety, if not treated, will have an impact on the health of the mother and fetus. Family support plays an important role in helping mothers adapt. Based on a preliminary study at the Mulyorejo Health Center, 10 out of 12 (83.33%) pregnant women still experience anxiety before childbirth, so this study aims to analyze the relationship between family support and pregnancy anxiety in the third trimester at the Mulyorejo Health Center. This type of study was quantitative observational analysis with a cross sectional method on 32 respondents. The instruments used were the Family Support Pregnancy Questionnaire modification questionnaire and the PRAQ-R2 modified questionnaire, with Spearman Rho analysis. The results showed that most of the respondents had family support both (93.75%) and moderate anxiety (50.00%), it was found that information support was the highest aspect and emotional support was the lowest aspect, as well as the highest anxiety related to contractions and childbirth. The results of the Spearman correlation test showed no significant association between family support and pregnancy anxiety (p = 0.453 and r = 0.137), so anxiety was also affected by other factors outside of family support. Keywords: Family support, Pregnancy anxiety, Trimester III